SHORT AND MID-TERM MEDICAL OUTCOMES OF SLEEVE GASTRECTOMY IN OBESITY IN SULAIMANI CITY. AN ANALYTICAL CROSS-SECTIONAL STUDY - Ahmed, Syamand Awrahman; Abdullah, Karzan Seerwan; Gubarii, Mohammed Ibrahim Mohialdeen (Journal of Sulaimani Medical College, 2022)
Background The laparoscopic sleeve gastrectomy (LSG) is a frequently performed bariatric procedure. Studies indicate that LSG can facilitate successful and sustainable weight loss. Objectives To examine the short-term (weight reduction) and mid-term (weight maintenance, quality of life, and medical conditions) outcomes following sleeve gastrectomy in Sulaimani. Patients and Methods A cross-sectional study was conducted on 114 participants from both high-quality and Zhyan hospitals in Sulaimani. From Feb 3, 2020, to Jul 22, 2021, data was gathered by evaluating the patient data records of 114 patients. Data included patients’ demographics, preoperative BMI& comorbidities, complications, and weight loss in the first week, second,4th, sixth months, and sixth months. Also, after the sixth month, complications were recorded and analyzed by SPSS software (IBM, version 25), including frequency and percentage, mean, and standard deviation, also obtained for parametric data. The associations between the variables were tested at a P value <0.05. Results The study consists of 114 patients (71.9% female and 28.1% male), with an average age of 34.0 years (range 20- 51 years). The average preoperative BMI and weight were 41.2 kg/m2 and 110.80 kg, respectively. Six months after surgery, the average ± SD of BMI was 32.8 kg/m ± 2 4.5, and the average ± SD of weight was 87.8 kg ±14.4. The prevalence of early postoperative problems (leak, upper GI bleeding, and intraperitoneal hemorrhage) among 114 patients was 0.9% for each complication, while the proportion of early postoperative nausea was 66.7%, and vomiting was 39.5%. Preoperative sleep apnea was 34.2%; after six months of surgery, the percentage was 0%; 19.3% of patients had joint pain; after six months of surgery, the percentage was 0.9%. In addition, 14 out of 114 patients (12.3%) had preoperative Hypertension, and 2 out of 114 patients (1.75%) had diabetes; after six months, 50% of both groups discontinued medical treatment. The incidence of gallstone development six months after surgery was 13.2%. Six months following LSG, 68.4% of individuals had hair loss. Conclusion laparoscopic sleeve gastrectomy can considerably reduce BMI six months following surgery and may help improve or eliminate obesity-related comorbidities such as Hypertension and type 2 diabetes. A laparoscopic sleeve gastrectomy is an effective option for obese adults, resulting in significant weight loss with a low incidence of postoperative complications. LSG could be recommended as a valuable single intervention therapy for patients who typically fail to achieve and obtain real benefits from a structured weight loss program.
Keywords: Obesity; sleeve gastrectomy; medical outcomes